2020
DOI: 10.3390/e22010094
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sensing Method Based on Information Geometry and Deep Neural Network

Abstract: Due to the scarcity of radio spectrum resources and the growing demand, the use of spectrum sensing technology to improve the utilization of spectrum resources has become a hot research topic. In order to improve the utilization of spectrum resources, this paper proposes a spectrum sensing method that combines information geometry and deep learning. Firstly, the covariance matrix of the sensing signal is projected onto the statistical manifold. Each sensing signal can be regarded as a point on the manifold. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Consequently, numerous researchers have investigated the combination of deep learning neural networks with spectrum-sensing research. For instance, in [14], scholars Kaixuan Du et al considered the geodetic distances between signals as statistical features and employed deep neural networks (DNNs) for classifying the data based on these distances, achieving spectrum sensing. Additionally, Jianxin Gai et al proposed a spectrum-sensing method based on residual networks (ResNets) in [15].…”
Section: Spectrum Decision Achieve the Optimal Transmission Strategymentioning
confidence: 99%
“…Consequently, numerous researchers have investigated the combination of deep learning neural networks with spectrum-sensing research. For instance, in [14], scholars Kaixuan Du et al considered the geodetic distances between signals as statistical features and employed deep neural networks (DNNs) for classifying the data based on these distances, achieving spectrum sensing. Additionally, Jianxin Gai et al proposed a spectrum-sensing method based on residual networks (ResNets) in [15].…”
Section: Spectrum Decision Achieve the Optimal Transmission Strategymentioning
confidence: 99%
“…Du et al [27] presented a new approach which uses information geometry and deep learning for spectrum sensing. In first stage, covariance matrix is computed and later geodesic distance is computed between signals which is considered as feature vector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers of the papers [19] [20] [21], dedicated to theparallel evolution simulation model of algorithm of dust particles in campus environment, indicated that the basic idea of the Monte-Carlo method is that the solution of the problem is equivalent to a hypothetical-statistical model parameter which can be calculated by using random number, and the parameters are estimated by the statistical model of a testing sample. The paper [22] is proposed a spectrum sensing algorithm based on a deep learning convolutional neural network, which avoided the influence of the accuracy of the hypothetical-statistical model on the detection results and improved the detection probability. The researchers of the work [23] noted that Eco-Driving, a driver behavior-based method, has featured in a number of national policy documents as part of CO 2 emissions reduction or climate change strategies.…”
Section: Literature Reviewmentioning
confidence: 99%